Husband And Wife's Rights in Gender Study: Study of The Islamic Fiqh Wa Adilatuhu by Wahbah Azzuhaili - Lahutiy, Sabrina; Wulandari, Yunita (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Gender inequality remains a significant societal issue. Men often assert dominance over their wives using religious and cultural arguments without critically evaluating existing texts or considering contemporary developments. This leads to gender injustice, including a double burden and the marginalization of women. The misconception of male superiority also contributes to domestic violence. . This research was conducted to determine the relevance of books written by contemporary ulama to the current era and to find out whether there is gender inequality in the explanation of these books. This study employs a qualitative library research methodology to examine the rights of husbands and wives as presented in the Islamic book: Al- fiqh al-islam waadilatuhu. The findings reveal a discrepancy between some of Sheikh Wahbah Zuhaili's explanations regarding husband and wife rights and contemporary realities in his work Fiqh Islam Waadilatuhu. Several of these explanations, rooted in classical fiqh texts, contribute to gender inequality. Therefore, a critical review of these texts is needed to provide a modern and relevant understanding. [Saat ini banyak sekali isu terkait ketimpangan gender di masyarakat. Laki-laki mendominasi istri menggunakan dalil agama dan budaya tanpa mengkaji kembali teks yang ada serta tidak melakukan pendekatan kritis terhadap perkembangan zaman. Hal tersebut menjadikan seorang istri mendapatkan ketidakadilan gender, selain mendapat beban ganda perempuan juga termarginalisasikan. Bahkan dengan pemahaman bahwa laki-laki lebih superior dibandingkan Perempuan banyak sekali terjadi KDRT. Penelitian ini bertujuan untuk mengetahui kerelevanan kitab karya uama kontemporer dengan zaman saat ini dan untuk mengetahui apakah ada ketidaksetaraan gender dalam penjelasan kitab tersebut. Penelitian ini menggunakan metode kualitatif jenis library research untuk mengkaji hak suami dan istri dalam kitab fiqh islam waadilatuhu. Temuan penelitian ini ketidakrelevanan beberapa pemaparan syekh Wahbah zuhaili dalam hak suami istri dalam karyanya kitab Fiqh Islam Waadilatuhu dengan konteks masyarakat modern. Dimana beberapa penjelasan mengenai hak suami istri dalam kitab tersebut masih berpacu pada kitab fiqh klasik. Sehingga hal tersebut memicu adanya ketimpangan gender.]